(untitled) (Journal of the College of Basic Education, 2026)
Discussion of the contract theory as one of the common theories, which includes research on transactions such as sale, lease, mortgage, companies, loans, agency, guarantee, and other matters related to contracts. The contract is one of the reasons for transferring ownership, and it is the creator of obligations and rights. It is also a legal officer for ending disputes. It has scientific importance that makes it important in legal, jurisprudential and fundamentalist discussions. Our discussion of the theory deals with the general lines of the theory and its obligations, and does not expand greatly, because the topic under study has many and varied aspects. It was necessary for the discussion to include three demands, which show the reader a general concept of the theory, and what are the titles that fall under the title of the theory.